2010
DOI: 10.1159/000274377
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Sonography of Uterine Arteries at 20–23 Weeks: Depth of Notch Gives Information on Probability of Adverse Pregnancy Outcome and Degree of Fetal Growth Restriction in a Low-Risk Population

Abstract: Objective: Our purpose was to assess the relation between the depth of notch in the uterine arteries at 20–23 weeks and the incidence and severity of subsequent pregnancy complications. Methods: The Notch Index (NI) was defined as (C – D)/C, with C = postsystolic zenith and D = postsystolic nadir. For evaluation, the mean NI of the two uterine arteries was determined. Adverse pregnancy outcome was defined as presence of SGA ≤5th percentile, pre-eclampsia, preterm delivery <33 weeks, placental abruption or intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 92 publications
1
5
0
4
Order By: Relevance
“…Therefore, we believe that mNDI should be measured in additive to mPI, mRI and BN for increasing accuracy to predict placental diseases related with placental dysfunction. However, our cohorts were relative smaller numbers than those in recent clinical studies using the mPI; 3,4,6,14 therefore, our results should be validated in a larger cohort study.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, we believe that mNDI should be measured in additive to mPI, mRI and BN for increasing accuracy to predict placental diseases related with placental dysfunction. However, our cohorts were relative smaller numbers than those in recent clinical studies using the mPI; 3,4,6,14 therefore, our results should be validated in a larger cohort study.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, some studies indicated that the depth of the notch could predict the perinatal outcome. Becker and Vonk [3] found that deep notching in the uterine arteries at 20 -23 weeks was associated with adverse pregnancy outcome. In contrast, Ghosh et al [12] suggested that the uteroplacental vascular impedance was a better predictor than the presence of notching in the third trimester for adverse outcome of SGA suspected pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…El presente estudio se planteó con la finalidad de establecer si hay cambios en la prevalencia de las alteraciones del Doppler de arterias uterinas en el segundo trimestre en pacientes categorizadas como bajo riesgo debido a que la población estudiada tiene diferencias sociodemográficas y de clasificación con respecto a los estudios previamente realizados (3,4,9).…”
Section: Discussionunclassified
“…Se considera alto riesgo obstétrico aquellas pacientes con: 1 factor de riesgo alto para trastornos hipertensivos asociados al embarazo o presencia de dos o más factores de riesgo moderados para esta condición, pacientes con puntuación ≥ 3 en la escala de Herrera y Hurtado o alto riesgo para trabajo de parto pre -término por presencia factores de riesgo reproductivos y ginecológicos (1,2). Las pacientes que no cumplen con los anteriores criterios son consideradas de bajo riesgo obstétrico; sin embargo, en la práctica clínica se observan desenlaces maternos o fetales adversos en esta población (3,4). En las poblaciones de bajo riesgo obstétrico se han visto desenlaces adversos como: preclampsia, restricción del crecimiento intrauterino, feto pequeño para la edad gestacional (FPEG), parto pretérmino < de 33 semanas, muerte fetal intrauterina y desprendimiento de placenta; todas estas, condiciones asociadas a la alteración en la invasión del trofoblasto (3,4,5,6).…”
Section: Introductionunclassified
See 1 more Smart Citation